Aspek Sosial Budaya dalam Penyelenggaraan Penyuluhan: Kasus Petani di Lahan Marjinal - Amanah, Siti; L. Hastuti, Endang; Basuno, Edi (Sodality: Jurnal Sosiologi Pedesaan, 2008)
This article focuses on explanation about socio-cultural aspects on the implementation of agricultural extension on farmers living on marginal lands. The paper was based on the research conducted on two population of farmers, in Bogor and Pontianak. Survey methods was used to collect data from 140 farmers’ respondents. Results research showed that farmers in marginal lands ran their business in small scale, the ownership of the lands was less than 0.5 hectares, farmers living condition were in low level soscio-economic condition. There were significant correlation between the dyamic of socio cultural condition, strength agricultural policy, extension workers competency, farmers business with the farmers competency in managing the lands for agricultural business. To promote better condition of farmers in marginal lands, agricultural extension institution should be strengthened and extension workers capacity needed to develop to facilitate the change in terms of increasing the productivity lands to improve farmers welfare and conserving the environment as well.